Tree type and forest management effects on structure of stream wood following wildfires - Vaz, P. (2012)
Wildfires are an increasingly common disturbance influencing wood recruitment to streams, and thereby affecting their physical and biological condition. Mediterranean countries such as Portugal, where more than 25% of the land area has burned since 1990, are ideal areas to study impacts of wildfire effects on streams. We evaluated the physical structure of 2206 downed wood pieces (DWP) across 27 first- to third-order streams in central Portugal, all of which had experienced recent wildfires. The streams flowed through monospecific upland forests of Eucalyptus, Maritime pines, or Cork oaks and were fringed by a mixture of riparian tree species. DWP structure differed between tree types and between burned and unburned pieces. Post-fire timber-production forests (Maritime pines and Eucalyptus) contributed a higher quantity of thinner, longer and straighter DWP to streams than Cork oak stands. Pieces from Maritime pines had more rootwads and branches than DWP from the other tree types. Pieces from Cork oak and riparian species generally had a bent form, were shorter and had no rootwads. Burned DWP in streams were often from riparian trees. Relative to unburned DWP, the burned DWP occurred more frequently, were larger and straighter, had branches less often, and were more decayed. With more complex branches, rootwads, and a larger diameter, inputs from burned Maritime pine forests are more likely to change stream hydraulics and habitat complexity, relative to inputs from Eucalyptus forests with their simpler structure. This study shows that, less than a decade after wildfires, structure of downed wood in and near streams is strongly influenced by wildfire, but also still reflects intrinsic species characteristics and respective silviculture practices, even after the effects of fire have been accounted for. Under an anticipated shift in landscape cover with higher shrubland proportions and more mixing of Maritime pine and Eucalyptus forests, our results suggest that instream large wood will become scarcer and more structurally homogeneous.